2019
DOI: 10.1002/nop2.396
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and its associated factors among  older people of selected ward of Banepa municipality, Nepal

Abstract: Aims The aim of this study was to calculate the prevalence of insomnia and identify the factors associated with it among older people of Banepa Municipality, Province No.3 of Nepal. Design A quantitative descriptive cross‐sectional study was done; data were collected for three months from September–November 2018. Methods One hundred and fourteen older people were recruited. The data were collected through a structured interview questionnaire that included socio‐demographic characteristics and Nepalese version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
3
10
1
Order By: Relevance
“…In the present study, we observed that monthly income was a risk factor for both depression and insomnia, indicating that participants with lower monthly income had a greater likelihood of developing depressive and insomnia symptoms, respectively. Our finding is consistent with several studies and confirms the evidence that depressive [6,16] and insomnia symptoms [19,22] in elderly people are associated with lower socioeconomic status, especially when assessed by indicators of material standards of living. A recent longitudinal study in 7,505 Chinese elderly people by Wang et al [14] showed a significant correlation between less wealth estimated by household income and depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we observed that monthly income was a risk factor for both depression and insomnia, indicating that participants with lower monthly income had a greater likelihood of developing depressive and insomnia symptoms, respectively. Our finding is consistent with several studies and confirms the evidence that depressive [6,16] and insomnia symptoms [19,22] in elderly people are associated with lower socioeconomic status, especially when assessed by indicators of material standards of living. A recent longitudinal study in 7,505 Chinese elderly people by Wang et al [14] showed a significant correlation between less wealth estimated by household income and depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…In this line, a nationwide epidemiological study in South Korea by Kim et al [ 18 ] found that sleep problems and insomnia among the elderly were closely related to their lifetime history of physical illness. Additionally, in a recent community-based study conducted by Dangol et al [ 22 ] among Nepalese older adults, both the presence of comorbid diseases and the use of regular medicine at present were positively associated with insomnia. In general, the existing body of literature suggests that poor health status in the elderly is significantly associated with a higher likelihood of suffering from insomnia symptoms [ 19 ].…”
Section: Discussionmentioning
confidence: 98%
“…The Prevalence of sleep disorder of this study was 75%, which is supported by the study conducted in old age home of Pashupati showing prevalence of insomnia 61.1% (Shrestha et al, 2017). Also, a study conducted in Banepa shows similar result of prevalence of insomnia which is 71.1% (Dangol et al, 2019). In present study, 43.3% of the female and 31.7% of the male population were affected by sleep disorder.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to lowering the overall quality of life, inadequate or poor sleep can decrease immunological function and increase the risk of cardiovascular disease, among other problems (Sim et al, 2019). To lower mortality, enhance quality of life, and improve sleep for these patients, it is critical to comprehend insomnia and how it relates to other issues (Dangol et al, 2020). Prognostic classification and treatment choices may benefit from the information that functional status can offer (Unruh, 2019).…”
Section: Significance Of Studymentioning
confidence: 99%